Analysis of variation in reference evapotranspiration and its driving factors in mainland China from 1960 to 2016. (22nd April 2021) - Wu, Dong; Fang, Shibo; Tong, Xingyuan; Wang, Lei; Zhuo, Wen; Pei, Zhifang; Wu, Yingjie; Zhang, Ju; Li, Mengqian
Abstract: Understanding the variation in reference evapotranspiration (ETo ) is vital for hydrological cycles, drought monitoring, and water resource management. With 1507 meteorological stations and 130 radiation-measured stations, the annual and seasonal ETo were calculated at each site from 1960 to 2016 in mainland China. The phenomenon of coefficient ' a ' being less than 0.25 and coefficient ' b ' being greater than 0.50 in the Angstrom–Prescott model occurred in almost the whole country, except for a small area of western and northeastern China. Moreover, the Xiao's method was more applicable to calculate the net longwave radiation ( R nl ) and then improve the estimation accuracy of ETo . The annual ETo varied from 538.8 to 1559.8 mm and had a high-value center located in the plateau and desert of northwestern China and a low-value center located in Northeast China and near the Sichuan Basin. The spatial distribution of seasonal ETo was roughly similar to that of annual ETo, except for that in winter when ETo was high in the south and low in the north. In mainland China, the annual ETo decreased by 21.2 mm decade −1 because of the declining sunshine duration before 1993 and increased by 21.1 mm decade −1 due to the decreased relative humidity (RH) after 1993. Generally, the abrupt change of ETo mainly occurred in the southern China rather than northern China (except for Qinghai Tibet Plateau). Basically, the dominant driving factors of annual and seasonal ETo were RH and/or T max after the abrupt change in most parts of China.